Changes Over Time in Sex Assignment for Disorders of Sex Development - GÜRAN, TÜLAY (AMER ACAD PEDIATRICS, 2014)
BACKGROUND AND OBJECTIVE: It is unclear whether the proportion of infants with a disorder of sex development who are raised as male or female has changed over time. The temporal trends in sex assignment of affected cases entered in the International Disorder of Sex Development (I-DSD) Registry were studied. METHODS: Cases of disorders of sex development reported as partial androgen insensitivity syndrome (PAIS; n = 118), disorder of gonadal development (DGD; n = 232), and disorder of androgen synthesis (DAS; n = 104) were divided into those who were born before 1990, 1990-1999, and after 1999. External appearance of the genitalia was described by the external masculinization score. RESULTS: The median (5th-95th percentile) external masculinization scores of those infants with PAIS, DGD, and DAS who were raised as boys were 6 (2-9), 6 (3-9), and 6 (1-12), respectively, and were significantly higher than in those raised as girls (2 [0-6], 2 [0-7], and 0 [0-5], respectively); this difference was maintained in the 3 temporal birth cohorts (P < .01). Of the 118 cases in the pre-1990 cohort, 41 (35%) were raised as boys; of the 148 cases in the 1990-1999 cohort, 60 (41%) were raised as boys; and of the 188 cases in the post-1999 cohort, 128 (68%) were raised as boys. CONCLUSIONS: Although there is an association between the external appearance of the genitalia and the choice of sex assignment, there are clear temporal trends in this practice pointing toward an increased likelihood of affected infants being raised as boys. The impact of this change in practice on long-term health outcomes requires additional focus.
Keywords: atypical; differences; DSD; gender; genitalia; intersex; CLOACAL EXSTROPHY; GENDER ASSIGNMENT; IDENTITY; INTERSEX; MALES; 46,XY; CONSEQUENCES; CONSENSUS